New media and their role in promoting a music product - Fedosenko, Karina (Ukrainian Cultural Studies, 2022)
Modern culture develops in close connection with digital technologies. Due to the fact that the Internet is now global in nature and covers various areas of human production, its comprehensive use is an urgent need for various industries. The use of social networks as an element of Internet marketing is highly effective, because they are flexible and available around the clock. The range of information that can be distributed in social networks is wide, including video, audio, and verbal texts. The cost of such distribution of media content will be extremely low, and at the same time, the circle of recipients, that can be reached, is quite a lot. Thanks to tracking, which consists in analyzing the behavior of website visitors, it is possible to understand ways to improve products. Targeting itself forms the practice of delivering advertising to the target audience. And besides, it is possible to shape virtual communities, groups that will be interested in consuming a media product. As a result of the Covid-19 pandemic, there have been changes in the music industry. The cancellation of concert activities, and the organization of different awards, contributed to the increase in the number of listening to music content with the help of specialized platforms. Social networks have also become a relevant tool for content distribution. Among the resources that increase the interest of performers is the practice of streaming. In fact, streaming is an online version of live broadcasting, that is a live reproduction of events that take place somewhere in the world and is offered for remote viewing. The only difference is that broadcasting used to be possible through radio and TV networks, but streaming is a streaming online transmission. Typically, this requires a certain streaming platform. This is the name of the service, which is used to transfer content from the provider to the user. At the same time, there is no need to download the content that is being broadcast. Real-time transmission allows you to receive video and audio content. Similar opportunities are available on such platforms as YouTube live, Instagram, TikTok, Twitch, Periscope, Facebook live. A number of them are focused mostly on game content and its distribution.
Keywords: culture; Internet; marketing; new media; musical product